THE NEED TO USE INTERACTIVE METHODS IN TEACHING PRIMARY CLASS STUDENTS - Nabiyeva Dilfuza Temirovna (Scholar Express Journals, 2023)
This article examines the issues of how to effectively organize lessons for elementary school students using interactive methods and methods that are part of modern innovation technologies.
Keywords: Modern innovation technologies; interactive methods and methods; elementary school students